Guinea-Bissau : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This report describes recent economic and financial developments in Guinea-Bissau, focusing on 1994 and early 1995, and provides statistical coverage from 1990. In 1994, the rate of growth of aggregate economic output exceeded that of the population, the pace of consumer price inflation abated to historic low, and both the fiscal and external current account positions showed further improvement. At end-1994, the economic and financial situation of Guinea-Bissau remained characterized by large domestic and external imbalances, as well as by a heavy burden of external debt service obligations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet